Redes sociais, mercado e cultura migratória: um estudo sobre fatores associados à mobilidade populacional na microrregião de Governador Valadares no século XXI - Leonardo Gomes de Sousa (2016)
The aim of this investigation is to comprehend how the international migration regime in Governador Valadares micro region remained the same during the decade between 2000 and 2010, observing the occurrence of several economic events on the source and destination that promotes changes in international migration flow and volume. The results of this research are organized into three articles, preceded by a general introduction and ending with a brief conclusion. The first article sought to verify the consistency of this migratory paradox through theoretical analysis of migration, the regional reality and verification of census data and others primary sources. The analysis pointed out that international migration in the region occurred in this decade due mainly to two factors: the role of returned migrants in the migration system and diffusion of values and attitudes which make up the so called migration culture. Thus, the second article utilized the perspective of Social Network Analysis to verify the importance of the returned migrants to carry out the implementation of social support on the migration system. The relational approach pointed out that the returned migrants mediates of strategic resources transmitted in the community, being characterized as an actor endowed with unique social capital within the migration system, and may take financial support roles, psychological, brokering among other contacts, and reproduction of an industry of illegal migration.The third article used a cognitive analytical model about the culture of migration applied to demographic studies through the creation a nested network of meanings. The overall network presented a betweenness centralization measure mainly guided by the objects: Labour, Better Life, Money, Longing and United States. It is also noted that the spreading of the values and attitudes that feeds the migratory culture in the region is well established in various population subgroups. These three articles emphasize the power of perpetuating mechanisms in migration systems, which for the case analyzed were able to maintain a significant flow of migrants even in a time of several oscillations between origin and destination.